DOKTRIN ALKITAB: FONDASI IMAN KRISTEN DAN RELEVANSINYA MASA KINI - Artha Yualin; Ernawati; Dina Sosialita; Sarmauli (Adisam Publisher, 2025)
This journal article aims to systematically explore the doctrine of the Bible (Bibliology) as the foundational pillar of the Christian faith and its relevance for believers today. The central problem addressed is the waning acknowledgment of the Bible's authority in the postmodern era, marked by rationalist skepticism, liberal interpretations, and a practical neglect of Scripture in daily life. Employing a qualitative literature research method, this study draws upon theological works from figures such as Louis Berkhof, Henry C. Thiessen, and Paul Enns. The findings indicate that the Bible, composed of the Old and New Testaments written over 1,500 years by more than 40 authors, demonstrates a remarkable unity centered on God's salvation plan through Jesus Christ. As God-breathed Scripture (theopneustos), it possesses divine attributes: authority, inerrancy, sufficiency, clarity, necessity, and eternality. The study concludes that Bibliology is not merely an academic discipline but a crucial doctrine that shapes the believer's faith, provides ethical standards, offers comfort, and motivates mission. Its application in personal, family, church, and societal life ensures that the Christian faith remains robust and relevant amidst contemporary challenges